Maria, segno di sicura speranza e di consolazione. La ricezione della Lumen Gentium, n. 68 - Charamsa, Krzysztof (Alpha Omega, 2012)
The contribution deals, in the first place, with the post-conciliar reception of the shortest article of the Dogmatic Constitution Lumen gentium, n. 68, which addresses the issue of the meaning of the glorious state of Mary for the Church. This reception shows that the theme of the Virgin Mary as a sign of sure hope has met a renewed interest and a significantly deeper understanding, especially from the papal magisterium and from a greater involvement of such Marian truth in the liturgy of the Church, thus opening up a new challenge to theological thought and to ecumenical dialogue.